Utilization of Nata De Coco as Adsorben in Methyl Orange Adsorption - Sani Widyastuti Pratiwi; Siska Novita Sari; Ratna Nurmalasari; Meli Indriani (EduChemia (Jurnal Kimia dan Pendidikan), 2020)
Methyl Orange was a textile waste that polluted the environment and harmed aquatic ecosystems and human life. It could affect the photosynthesis of oxygen regeneration and disrupt the biological activity of microbes in the water. One of the ways to deal with these wastes by adsorption using  Nata de coco. Nata de coco was used as an alternative adsorbent made from cellulose, which was a waste of coconut water in the process of making it easy, inexpensive, and biodegradable. This study aims to determine the effect of contact time and mass of  Nata de coco adsorbents on the adsorption of methyl orange. This research method includes three stages were adsorbent preparation, adsorption, and UV-Vis spectrometer analysis. The adsorption process was carried out with contact time variations of 30 and 60 minutes, variations in the mass of the adsorbent 0.05g; 0.1g; and 0.15g. The results showed the optimum adsorption conditions occurred at 60 minutes of contact time and an adsorbent mass of 0.15g with an adsorption efficiency of 44.66% and an adsorption capacity of 0.2066 mg/g.